The theory of elastic waves and waveguides - Miklowitz, Julius, 1919- (North-Holland series in applied mathematics and mechanics, 1984)
The primary objective of this book is to give the reader a basic understanding of waves and their propagation in a linear elastic continuum. The studies of elastodynamic theory and its application to fundamental value problems should prepare the reader to tackle many physical problems of general interest in engineering and geophysics, and of particular interest in mechanics and seismology.